Prenatal diagnosis of chronic intestinal pseudo‐obstruction and paternal somatic mosaicism for the ACTG2 pathogenic variant. (28th November 2017) - Milunsky, Aubrey; Lazier, Joanna; Baldwin, Clinton; Young, Carmen; Primack, Daniel; Milunsky, Jeff M.
Abstract : What's already known about this topic? Pathogenic variants in the ACTG2 gene cause highly variable autosomal dominant phenotypes from intestinal pseudo‐obstruction to megacystis to constipation. Pathogenic variants in rarer recessive genes ( MYH11, MYLK, RAD21, and LMOD1 ) cause similar phenotypes. What does this study add? Autosomal dominant pathogenic variants in the ACTG2 gene may originate from an asymptomatic parent who has somatic mosaicism for this gene mutation, resulting in megacystis‐microcolon‐hypoperistalsis syndrome. Prenatal diagnosis can be offered when fetal bladder prominence is observed.